Where the red fern grows : the story of two dogs and a boy : with connections - Rawls, Wilson (USA : Random House Childres's Books, 2001)
A young boy living in the Ozarks achieves his heart's desire when he becomes the owner of two redbone hounds and teaches them to be champion hunters.
Novel, followed by narratives and excerpts from related stories and a biographical sketch of the author.
Keywords: Hounds -- Fiction; Dogs -- Fiction; Ozark Mountains -- Fiction